1994
DOI: 10.1021/ja00089a047
|View full text |Cite
|
Sign up to set email alerts
|

Dinitrogen Reduction Operated by a Samarium Macrocyclic Complex. Encapsulation of Dinitrogen into a Sm2Li4 Metallic Cage

Abstract: In spite of the considerable number of dinitrogen complexes reported since the discovery of the first example of dinitrogen fixation in [ R u ( N H~)~]~+ 30 years ago,' the chemistry of Nz still remains in its infancy. However, new perspectives for the metalpromoted activation fixation of dinitrogen are opening up, as has been recently seen in both the reversible dinitrogen activation operated by the lithium countercation of an anionic Zr(II1) complex2 and the considerable reduction of NZ performed by electron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
70
0
5

Year Published

1999
1999
2012
2012

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 121 publications
(79 citation statements)
references
References 2 publications
4
70
0
5
Order By: Relevance
“…Reaction of the ªgreen complexº with N 2 leads to an interesting dinitrogen compound. [80] The NÀN distance of the complexed nitrogen is 1.525(4) , which is in agreement with an NÀN single bond. This means that a four-electron reduction has taken place.…”
Section: Reviewssupporting
confidence: 67%
“…Reaction of the ªgreen complexº with N 2 leads to an interesting dinitrogen compound. [80] The NÀN distance of the complexed nitrogen is 1.525(4) , which is in agreement with an NÀN single bond. This means that a four-electron reduction has taken place.…”
Section: Reviewssupporting
confidence: 67%
“…However, the addition to 2'-methoxyacetophenone afforded 10 b in an excellent yield of 93 % (Table 5, entry 2), which can be attributed to the ortho-chelate effect of the substrate, which presumably facilitated the coordination of 2'-me-A C H T U N G T R E N N U N G thoxyA C H T U N G T R E N N U N G acetophenone to the active metal center. For heteroaromatic ketones, the a-hydroxy phosphonates 10 n-10 r were also obtained in good yields (Table 5, entries [14][15][16][17][18]. It is worth noting that a series of a-hydroxy diaryl phosphonates could also be obtained in high yields through additions of diethyl phosphite to substituted benzophenones in the presence of the yttrium amide 2 as a catalyst (Table 5, entries [19][20][21][22][23][24], except in the case of 2,4'-difluorobenzophenone (51 % yield, entry 23), probably due to steric hindrance of the substrate.…”
Section: Resultsmentioning
confidence: 99%
“…[13] It has been demonstrated that lanthanide complexes containing pyrrolide ligands produced unexpected structures and displayed various reactivities with regard to polymerization, reduction of N 2 , and reversible fixation of ethylene. [14] We have reported that methylene-linked pyrrolyl lanthanide amido complexes were able to catalyze additions of the NÀH bond of the amines to carbodiimides. [15] Here we report the synthesis and characterization of rare earth metal amides with methylene-linked pyrrolyl-amido ligands exhibiting h 1 and h 5 bonding modes, together with their first applications as catalysts for hydrophosphonylations of aldehydes and unactivated ketones.…”
mentioning
confidence: 99%
“…[59] The reaction of lithium with [(Oepg)ClSm(µ 3 -Cl)Li 3 (THF) 4 ] [formed in situ by reaction of SmCl 3 (THF) 3 and OepgLi 4 ] under nitrogen resulted in nitrogen reduction and the formation of an Sm III complex containing a tetralithium hydrazide, [{(Oepg)SmLi (THF) 2 } 2 (N 2 Li 4 )] (73), presumably through a transient Sm II species which is reoxidized to Sm III by means of an electron transfer to N 2 . [60] A different series of complexes was obtained when the reaction stoichiometry of Sm and Oepg is 2:1. The reaction of 2 equivalents of SmCl 3 (THF) 3 76), was isolated.…”
Section: B Macrocyclic Tetrapyrrolyl Complexesmentioning
confidence: 99%